Manometric Measurement of the Sphincter of Oddi in Patients with Common Bile Duct Stones: A Consecutive Study of the Han Population of China. (4th January 2017) - Feng, Yadong; Zhang, Jie; Jiao, Chunhua; Zhu, Hong; Cheng, Wenfang; Xu, Shunfu; Xiao, Bin; Ni, Jinliang; Chen, Xiaoxing
Abstract : Objective . Role of dysfunction of the sphincter of Oddi (SO) in choledocholithiasis is controversial. This study was to evaluate SO motor activity in patients with common bile duct (CBD) stones in the Han population of China. Patients and Methods . In this study, 76 patients with CBD stones were enrolled in a single tertiary endoscopy center. Data of SO motor activities was prospectively evaluated by endoscopic manometry. Mean basal SO pressure, amplitude, and frequency were collected and analyzed. Results . The mean basal SO pressure, amplitude, and frequency were 52 . 7 ± 40.0 (1.60–171.1) mmHg, 39.9 ± 19 . 7 (14.9–115.5) mmHg, and 5.7 ± 3.2 (1.3–13.8)/min, respectively. The basal SO pressure was higher in patients with CBD stones < 10 mm in diameter than that in those with CBD stones larger than 10 mm in diameter (60.7 ± 41.0 mmHg versus 36.8 ± 29.4 mmHg, P = 0.043 ). There was no significant difference in the basal SO pressure, amplitude, and frequency when compared with the CBD diameter, CBD stone number, prior cholecystectomy, periampullary diverticula, and symptoms. Levels of alanine aminotransferase, aspartate transaminase, γ -glutamyl transpeptidase, and alkaline phosphatase showed no significant difference in patients with normal or elevated basal SO pressure. Conclusion . These results identify that, in Chinese Han population, abnormalities of SO motor activity are associated with CBD stones.